Recent advances in targeting the prostacyclin pathway in pulmonary arterial hypertension - Irene M. Lang; Sean P. Gaine (European Respiratory Review, 2015)
Pulmonary arterial hypertension (PAH) is a severe disease characterised by increased pulmonary vascular resistance, which leads to restricted pulmonary arterial blood flow and elevated pulmonary arterial pressure. In patients with PAH, pulmonary concentrations of prostacyclin, a prostanoid that targets several receptors including the IP prostacyclin receptor, are reduced. To redress this balance, epoprostenol, a synthetic prostacyclin, or analogues of prostacyclin have been given therapeutically. These therapies improve exercise capacity, functional class and haemodynamic parameters. In addition, epoprostenol improves survival among patients with PAH. Despite their therapeutic benefits, treatments that target the prostacyclin pathway are underused. One key factor is their requirement for parenteral administration: continuous intravenous administration can lead to embolism and thrombosis; subcutaneous administration is associated with infusion-site pain; and inhalation is time consuming, requiring multiple daily administrations. Nevertheless, targeting the prostacyclin pathway is an important strategy for the management of PAH. The development of oral therapies for this pathway, as well as more user-friendly delivery devices, may alleviate some of the inconveniences. Continued improvements in therapeutic options will enable more patients with PAH to receive medication targeting the prostacyclin pathway.